Selected issues of access to public information in local government - Karciarz, Mateusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The right of access to public information is one of the fundamental constitutional civil rights in the Polish legal system. Its rules on practical implementation regulate the law of access to public information. With the increase of civic awareness among citizens there also follows a growth in applications for access to public information. This has caused a range of problems and doubts in interpretation, which local government bodies have to contend with when dealing with submitted applications. In this article the author presents the most common problems which local government bodies must face in practice.